Telekom Malaysia Berhad Excellence Award for Nur Aishah, Manufacturing Process Engineer - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
GAMBANG, 21 October 2023 – “No Pain No Gain” is the life principle held by Nur Aishah Baharudin, 24, a Bachelor (Hons) Electrical Engineering (Power Systems) graduand from the Faculty of Electrical and Electronics Engineering Technology, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).